DIPG-58. HISTONE H3 WILD-TYPE DIPG/DMG OVEREXPRESSING EZHIP EXTEND THE SPECTRUM OF DIFFUSE MIDLINE GLIOMAS WITH PRC2 INHIBITION BEYOND H3-K27M MUTATION. (4th December 2020) - Castel, David; Kergrohen, Thomas; Tauziède-Espariat, Arnault; Mackay, Alan; Ghermaoui, Samia; Lechapt, Emmanuèle; Pfister, Stefan; Kramm, Christof; Boddaert, Nathalie; Blauwblomme, Thomas; Puget, Stéphanie; Beccaria, Kévin; et al.
Abstract: Diffuse midline gliomas (DMG) H3 K27M-mutant were introduced in the 2016 WHO Classification unifying diffuse intrinsic pontine gliomas (DIPG) and gliomas from the thalamus and spinal cord harboring a histone H3-K27M mutation leading to Polycomb Repressor Complex 2 (PRC2) inhibition. However, few cases of DMG tumors presenting a H3K27 trimethylation loss, but lacking an H3-K27M mutation were reported. To address this question, we combined a retrospective cohort of 10 patients biopsied for a DIPG at the Necker Hospital or included in the BIOMEDE trial (NCT02233049) and extended our analysis to H3-wildtype (WT) diffuse gliomas from other midline locations presenting either H3K27 trimethylation loss or ACVR1 mutation from Necker, ICR, the HERBY trial, the INFORM registry study and the St. Jude PCGP representing 9 additional cases. Genomic profiling identified alterations frequently found in DMG, but none could explain the observed loss of H3K27 trimethylation. Similar observations were previously made in the PF-A subgroup of ependymoma, where the H3K27me3 loss resulted from EZHIP/CXorf67 overexpression rather than H3-K27M mutations. We thus analyzed EZHIP expression and observed its overexpression in all but one H3-WT DMGs compared to H3-K27M mutated tumors (EZHIP negative). Strikingly, based on their DNA methylation profiles, all H3-WT DMG samples analyzed clustered close to H3-K27M DIPG, rather than EZHIP overexpressing PF-A ependymomas. To conclude, we described a new subgroup of DMG lacking H3-K27M mutation, defined by H3K27 trimethylation loss and EZHIP overexpression that can be detected by IHC. We propose that these EZHIP/H3-WT DMGs extend the spectrum of DMG with PRC2 inhibition beyond H3-K27M mutation.